a) Xét : \(P^2=\frac{3\left(a-b\right)^2}{3\left(a+b\right)^2}=\frac{3\left(a^2+b^2\right)-6ab}{3\left(a^2+b^2\right)+6ab}=\frac{10ab-6ab}{10ab+6ab}=\frac{4ab}{16ab}=\frac{1}{4}\)
Vì a > b > 0 nên P > 0 . Vậy \(P=\frac{1}{2}\)
b) Tương tự.
a/ \(3a^2+3b^2=10ab\Leftrightarrow3\left(a^2+b^2\right)=10ab\Leftrightarrow a^2+b^2=\frac{10ab}{3}\)
\(\Leftrightarrow a^2+b^2-2ab=\frac{10ab}{3}-2ab\Leftrightarrow\left(a-b\right)^2=\frac{4ab}{3}\)
tương tự: \(a^2+b^2=\frac{10ab}{3}\Leftrightarrow a^2+b^2+2ab=\frac{10ab}{3}+2ab\Leftrightarrow\left(a+b\right)^2=\frac{16ab}{3}\)
\(\Rightarrow P^2=\left(\frac{a-b}{a+b}\right)^2=\frac{\frac{4ab}{3}}{\frac{16ab}{3}}=\frac{1}{4}\Rightarrow P=\frac{1}{2}\)
b/ \(2a^2+2b^2=5ab\Leftrightarrow2\left(a^2+b^2\right)=5ab\Leftrightarrow a^2+b^2=\frac{5ab}{2}\)
\(\Leftrightarrow a^2+b^2+2ab=\frac{5ab}{2}+2ab\Leftrightarrow\left(a+b\right)^2=\frac{9ab}{2}\)
tương tự: \(a^2+b^2=\frac{5ab}{2}\Leftrightarrow\left(a-b\right)^2=\frac{ab}{2}\)
\(\Rightarrow Q^2=\left(\frac{a+b}{a-b}\right)^2=\frac{\left(a+b\right)^2}{\left(a-b\right)^2}=\frac{\frac{9ab}{2}}{\frac{ab}{2}}=9\Rightarrow Q=3\)